Digital Learning Media in Interactive Multimedia Based on Inquiry Approach for Sociology Learning in High Schools - Pinilih, Yogi; Rejekiningsih, Triana; Musadad, Akhmad Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The rapid evolution of technology presents significant challenges in its integration into educational environments. Despite these challenges, interactive multimedia digital learning materials stand out as an effective means to meet educational objectives in high schools. By combining these materials with methodologies like inquiry-based learning, educators can offer a richer and more dynamic learning experience. Therefore, the objective of this research is to develop interactive multimedia with an inquiry-based approach that is suitable for use in education. The research method used in this study is research and development, adopting the Alessi & Trollip model. The research sample consist of 7 people which was media experts, subject matter experts, practitioners (subject teachers), and 42 students. Data collection is conducted through non-test methods such as observation and questionnaires. The research data is then analyzed qualitatively and quantitatively. The research results show that in the alpha testing phase, the developed interactive multimedia received a